Community health-care planning in Western Australian Country Health Service-South West: An evaluation of patient views - Hunt, E.; Moore, J.; Sherriff, Jillian (Wiley-Blackwell Publishing Asia, 2012)
Aims: To investigate community health patients' impressions of care planning and their relationship with allied health professionals in a rural town in Western Australia. Methods: Focus groups were conducted followed by a survey to identify patients' opinions on care planning and their relationships with health professionals. Results: Focus groups and a survey identified that patients generally had positive attitudes towards their experiences with community-based allied health professionals. Participants identified some of the attributes that they valued in allied health professionals. Many participants (39%) believed that they had a partnership with the health professional and also valued having a shared decision-making power with the health professional (46%); however, 17% identified that they would prefer the health professional to assume more of the decision-making power. Conclusions: More work is needed to create a health culture in which patients want to manage their own health and can develop a relationship with their health professional that allows them to achieve this.